Ensembles from Ordered and Disordered Proteins Reveal Similar Structural Constraints during Evolution. Issue 6 (15th March 2019) - Marchetti, Julia; Monzon, Alexander Miguel; Tosatto, Silvio C.E.; Parisi, Gustavo; Fornasari, María Silvina
Abstract: The conformations accessible to proteins are determined by the inter-residue interactions between amino acid residues. During evolution, structural constraints that are required for protein function providing biologically relevant information can exist. Here, we studied the proportion of sites evolving under structural constraints in two very different types of ensembles, those coming from ordered and disordered proteins. Using a structurally constrained model of protein evolution, we found that both types of ensembles show comparable, near 40%, number of positions evolving under structural constraints. Among these sites, 68% are in disordered regions and 57% of them show long-range inter-residue contacts. Also, we found that disordered ensembles are redundant in reference to their structurally constrained evolutionary information and could be described on average with 11 conformers. Despite the different complexity of the studied ensembles and proteins, the similar constraints reveal a comparable level of selective pressure to maintain their biological functions. These results highlight the importance of the evolutionary information to recover meaningful biological information to further characterize conformational ensembles. Graphical Abstract: Unlabelled Image Highlights: Ordered and disordered proteins show similar structural constraints during evolution. Alignments have meaningful evolutionary information about conformational ensembles. Experimentally obtained disordered ensembles could be redundant. Few stabilizing inter-residue contacts contain evolutionary information.